2011
DOI: 10.1097/mpg.0b013e3181e85b55
|View full text |Cite
|
Sign up to set email alerts
|

Cow's‐Milk Allergy Is a Risk Factor for the Development of FGIDs in Children

Abstract: CMA constitutes a risk factor for the development of FGIDs in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 26 publications
1
66
0
4
Order By: Relevance
“…proposed that various mechanisms such as genetics, early life events, environmental, gastrointestinal and psychosocial factors act together in a complex interplay ultimately resulting in an alteration to the gut-brain axis 10,11,12,13,14,15,16 . Afferent signals from the gastrointestinal tract transmitted via the pain pathways are subsequently amplified and the patient's perception of painful stimuli is in turn enhanced 17 .…”
Section: Pathophysiologymentioning
confidence: 99%
“…proposed that various mechanisms such as genetics, early life events, environmental, gastrointestinal and psychosocial factors act together in a complex interplay ultimately resulting in an alteration to the gut-brain axis 10,11,12,13,14,15,16 . Afferent signals from the gastrointestinal tract transmitted via the pain pathways are subsequently amplified and the patient's perception of painful stimuli is in turn enhanced 17 .…”
Section: Pathophysiologymentioning
confidence: 99%
“…In the first study of our series, we demonstrated that cow's milk protein hypersensitivity ---a common transient gastrointestinal inflammatory condition of infancy ---was a risk factor for the development of chronic abdominal pain and FGIDs later in childhood. 62 This case---control study included 52 subjects between 4 and 18 years of age who were diagnosed with cow's milk protein hypersensitivity within the first year of life. Fifty-three healthy siblings of the same age were selected as controls.…”
Section: Early Gastrointestinal Inflammation Trauma and Stressmentioning
confidence: 99%
“…Consequently, a low-allergen maternal diet or hypoallergenic infant formula have been proposed as a form of treatment (Hill 2005;Iacovou 2012;Schach 2002). Shannon 1921 first described the possibility of a relationship between infantile colic and allergens, and since then, a number of studies have evaluated the possible association between colic and food hypersensitivity (Heine 2013;Heine 2014;Hill 1995;Iacono 1991;Lothe 1982;Merras-Salmio 2013;Saps 2011). …”
Section: Description Of the Conditionmentioning
confidence: 99%